2010
DOI: 10.1093/toxsci/kfq067
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Dicarbonyls Generated in a Simulated Indoor Air Environment Using an In Vitro Exposure System

Abstract: Over the last two decades, there has been increasing awareness regarding the potential impact of indoor air pollution on health. Exposure to volatile organic compounds (VOCs) or oxygenated organic compounds formed from indoor chemistry has been suggested to contribute to adverse health effects. These studies use an in vitro monitoring system called VitroCell, to assess chemicals found in the indoor air environment. The structurally similar dicarbonyls diacetyl, 4-oxopentanal (4-OPA), glyoxal, glutaraldehyde, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
35
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 34 publications
2
35
0
Order By: Relevance
“…Cultex CG, Vitrocell, BAT) deposit particles from a continuous aerosol flow by diffusion and/or gravitational deposition onto cell cultures (Anderson et al, 2010;Aufderheide & Mohr, 1999;Muller et al, 2010;Phillips et al, 2005). Only few (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Cultex CG, Vitrocell, BAT) deposit particles from a continuous aerosol flow by diffusion and/or gravitational deposition onto cell cultures (Anderson et al, 2010;Aufderheide & Mohr, 1999;Muller et al, 2010;Phillips et al, 2005). Only few (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Various ALI exposure systems have been developed both in-house and commercially (Table 1) [6, 9, 12-18]. Each of the exposure systems shown in Table 1 uses different mechanisms to deposit particles, which include diffusion, sedimentation, cloud settling, and electrostatic precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in the field include the development of air/cell interface exposure systems such as those produced by companies including Vitrocell ® Systems (Waldkirch, Germany) and Cultex Laboratories (Hannover, Germany). These exposure systems allow for direct exposure (flowing system) of the apical surface of the cell line or tissue with the aerosolized compound of interest, eliminating the potential for chemical/media interactions (Anderson et al, 2010; Persoz et al, 2010; Schmalz et al, 2011). While these systems are highly efficient and sensitive they are often expensive and most do not easily allow for dose response studies.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro investigations into the specific health effects associated with exposure to secondary pollutants in the indoor environment are limited. One study conducted by Anderson et al (2010) demonstrated that exposure of A549 cells (Vitrocell ® for 4 h) to structurally similar terpene ozonolysis reaction products (dicarbonyl compounds) resulted in an increased pro-inflammatory response suggesting the potential for toxicity of secondary pollutants. The differences in exposure techniques and endpoints among the above mentioned studies emphasize the need for the standardization of this type of model.…”
Section: Introductionmentioning
confidence: 99%